THU0540 Screening of Familial Mediterranean Fever in Patients with Vertigo. (9th June 2015) - Haras, A.B.; Kucuk, A.; Turkmen, K.; Helvaci, A.; Tunc, R.
Abstract : Background: Familial Mediterranean fever is an autosomal recessive disease, characterized by recurrent attacks of fever and serositis. Generally, Sephardic Jews living in the mediterranean descent, Arabs, Turks, Armenians and other communities are affected by Familial Mediterranean Fever. It is characterized by abdomen, chest, joint, muscle aches associated with serositis and fever attacks. Vertigo is a frequent reason of admission to emergency services. Depending on the underlying problem, vertigo can be the sign of many diseases. Vertigo could be either psychological or pathological. Pathological Vertigo can be peripheral or central. Objectives: Familial Mediterranean Fever and vertigo shows clinical similarities. This study is built on the hypothesis that Familial Mediterranean Fever presents with serositis (including meninx), patients' admittion with atypical presentation such as dizziness associated with inflammation and ischemia, excluding classical symptoms such as abdominal and chest pain, synovial attack. Methods: 200 volunteered patients diagnosed with vertigo at the age of between 18-65 years who admitted to Neurology, Ear-Nose-Throat and Internal Medicine clinics of Meram Medical Faculty and Okmeydani Training and Research Hospital, and their same age in the group of 200 healthy volunteers that not diagnosed with vertigo were included in this study, their written and verbal informed consent obtained. Questionary were asked to the patients. Patients with middle ear problems, recurrent otitis media, chronic otitis media, use of ototoxic drugs, amyloidosis, diabetes mellitus, treatment of head and neck radiotherapy, medical history of acoustic trauma and workers exposed to noisy environment excluded from the study. Results: In 65 of the patients who diagnosed with vertigo had at least one of the symptoms of peritonitis, pleuritis or arthritis. In addition, 6 of the 65 patient had erysipel alike rash. Also in the control group, 44 volunteers had at least one of the symptoms of peritonitis, pleuritis or arthritis. However, none of these patients had erysipel alike rash. In the comparasion of two groups for the possible diagnosis of Familial Mediterranean Fever according to Tel – Hashomer criteria, the chi-square test was calculated as p=0.09, that shows no significant difference statistically. 3 of the 65 patient who diagnosed with vertigo that have at least one of the symptoms of peritonitis, pleuritis or arthritis, there was a history of Familial Mediterranean Fever shown in the 1st degree of relatives. In the control group, only 1 of the 44 patients has history of Familial Mediterranean Fever in their 1st degree of relatives In the comparasion of two groups for the possible diagnosis of Familial Mediterranean Fever according to Tel – Hashomer criteria, the chi-square test was calculated as p=0.09, that shows no significant difference statistically. Conclusions: With the data acquired, 8 of the patients in the vertigo group have met the criteria for probable diagnosis of Familial Mediterranean Fever. In the control group only 1 patient have met the criteria for probable diagnosis of Familial Mediterranean Fever. According to Tel- Hashomer criteria 1 patient in the vertigo group is comply with absolute diagnostic criteria; whereas in the control group there were no patient who meets the diagnostic criteria. Disclosure of Interest: None declared